Group Counseling with Cognitive Restructuring Technique to Improve The Self-Efficacy and Assertiveness of Students Who Experienced Advanced Study Anxiety (Universitas Negeri Semarang, 2019)
The purpose of this study was to examine the effectiveness of group counseling by using cognitive restructuring technique to improve self-efficacy and assertiveness of Junior High School Mardisiswa 2 Semarang who experienced advanced study anxiety. The quasi-experimental method pre-test – post-test design involving 16 students selected by purposive sampling. The result of data analysis showed that there was an enhancement in self-efficacy and assertiveness after the treatment. The acquisition shows that group counseling by using cognitive restructuring technique is effective to improve self-efficacy and assertiveness of students who experience advanced study anxiety.